Riding the hilltop: practical implementation and assessment of an implicit hilltop illusion - Vollette, Carole-Anne; Bockisch, Christopher J.; Bertolini, Giovanni (Frontiers in Neurology, 2025)
Passive motions can lead to conflicting combinations of visual and vestibular signals that can have a tremendous impact on our ability to navigate and comprehend the world. However, conflicting motion signals are also exploited for rehabilitation, adaptation training, and entertainment by creating functional illusions (VR, amusement parks). Low-frequency linear translations can induce “hilltop illusions,” a perceptual phenomenon consisting in a reinterpretation of the inertial acceleration as tilt with respect to gravity. Compared to other vestibular stimuli, the hilltop illusion has rarely been used as it is considered unpractical due to the complexity of the necessary motion devices, which can have high operational costs, induce cognitive biases jeopardizing the illusion and discomfort in the subject. We hypothesize that a practical protocol to create and quantify a hilltop illusion can be realized using low-frequency (0.16 Hz) small-amplitude (0.45 m) translations on a standard motion simulator (Stewart Platform), provided that expectations and awareness of the illusion are hindered. To this aim, we combined the lateral oscillations with 90° phase-shifted roll movement with a random direction and amplitude. A consistent tilt illusion was measured across 12 healthy participants (29.7 ± 14.5 yo, 6 females). The hilltop illusion was quantified using both haptic vertical (HV) and subjective visual vertical (SVV) assessments, showing a significant tilt perception with larger values displayed in HV (2.2° ± 1.2—gain to the GIA tilt = 41.8%) compared to SVV (0.51° ± 0.57—gain = 9.7%). The protocol was well tolerated, with minimal motion sickness reported. This new protocol offers an accessible method for the generation of an implicit vestibular illusion, while demonstrating the importance of preventing cognitive awareness of motion cues. It offers insights in the perceptual process of vestibular conflicts and provides a foundation for potential development of diagnostic and therapeutic applications, for training and for illusions.